THE EFFECT OF DURATION OF ACETYLCHOLINE-ESTERASE INHIBITOR ON MMSE, CDT AND BARTHEL INDEX SCORING ON PATIENTS WITH VASCULAR DEMENSIA - Sri Budhi Rianawati (University of Brawijaya, 2021)
Background: Vascular dementia is a cognitive decline with functional deterioration caused by cerebrovascular disease. It is the second leading cause of dementia. A number of screening questionnaires and models have been developed to help in assessing cognitive function and activity daily living (ADL) in patients with dementia. Mini Mental State Examination (MMSE), Clock Drawing Test (CDT) and Barthel Index are instruments to evaluate cognitive function and ADL of vascular dementia patients.